GAS CHROMATOGRAPHY-MASS SPECTROMETRIC ANALYSIS OF METHANOLIC LEAF EXTRACTS OF LANNEA KERSTINGII AND NAUCLEA DIDERRICHII, TWO MEDICINAL PLANTS USED FOR THE TREATMENT OF GASTROINTESTINAL TRACT INFECTIONS - Edewor Theresa Ibibia; Nimotalai Olabisi, Kazeem; OWA STEPHEN OLUWAGBEMIGA (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The leaves of Lannea kerstingii and Nauclea diderrichii are traditionally used for the treatment of gastrointestinal infections. The aim of this work is to determine the phytochemicals that are present in the leaves. Methods: Phytochemical screening was carried out to determine the type of phyto-components present while a gas chromatography-mass spectrometry (GC-MS) analysis was to separate and identify the different phytochemicals that are present in the leaves. Results: The phytochemical screening showed the presence of tannins, flavonoids, saponins, and steroids in the methanolic extracts of both plants while only steroids were present in the n-hexane extract of N. diderrichii. Alkaloids, anthraquinone glycosides, and terpenoids were absent in all extracts. The GC-MS revealed 16 compounds in the methanolic extract of L. kerstingii with dodecanoic acid, methyl ester as the predominant compound (24.276%) and 26 compounds in N. diderrichii with phenol, 2,4-bis(1,1-dimethylethyl) - (17.253%) as the most abundant. Seven compounds were identified to be common in the two plants methanol extracts. Some of the identified compounds possess biological activities. Conclusion: Some of the identified compounds could be responsible for the biological activity of the plants leaves, especially its effect on gastrointestinal pathogens. Keywords: Lannea kerstingii, Nauclea diderrichii, Gastrointestinal infection, Gas chromatography-mass spectrometri.